How to plan estate succession planning (Research, Society and Development, 2022)
Introduction: Succession planning is the legal instrument that allows the adoption of a strategy aimed at the effective and efficient transfer of a person's assets after their death. The general objective of this study is to analyze the means and methods of estate succession planning. Methodology: This study is defined as an exploratory research, with a qualitative approach, using a document analysis technique. Theoretical framework: In this topic, the general aspects of patrimonial succession will be addressed, as well as the means and methods that are related to it. Analysis of the Results: The presentation of the results aims to demonstrate the innovative approach adopted as a result of patrimonial succession, which aims to divide an individual's assets in life so that the will of the same person is fulfilled after death, thus avoiding long disputes. assets between family members. Final Considerations: In order to answer the question raised in the problem question, under the means and implications of patrimonial succession, this study aimed to unravel the aspects that surround the patrimonial succession, aspects that are focused on the general aspects and purposes, as well as the existing means that refer to succession.